JENIS TUMBUHAN SUMBER PAKAN LEBAH (Trigona sp.) DI DESA MIRRING POLEWALI MANDAR SULAWESI BARAT - Tahir, Hestia; Irundu, Daud; Rusmidin, Rusmidin (Jurnal Nusa Sylva, 2021)
The presence of feed and its availability is one of the keys to the successful management of Trigona sp. The presence and availability of feed can be seen from the diversity of feed-producing plants (pollen, nectar, resin). Mirring Village is one of the villages in Polewali Mandar which has the potential for Trigona sp. This study aims to identify and analyze the diversity of feed sources for Trigona sp. in Mirring Village. This research is quantitative research with purposive method. The results showed that there were 42 types of plant sources for bee Trigona sp.  found in coastal areas as many as 3 species  with INP 88.99 – 102.30 and H' 0.99, residential areas there are 30 species with INP 3.15 - 56.20 and H' 3.1, and in mountainous areas there are 18 type with IN 4.77 – 47.22 and H' 2.40. Based on the results for residential and mountainous areas, it is sufficient to provide a source of food, while the enrichment of plant species diversity as a source of food for Trigona sp bees is best carried out in coastal areas